Systematic Review of Cultural Aspects of Stigma and Mental Illness among Racial and Ethnic Minority Groups in the United States: Implications for Interventions - Misra, Supriya; Jackson, Valerie W.; Chong, Jeanette; Choe, Karen; Tay, Charisse; Wong, Jazmine; Yang, Lawrence H. (American journal of community psychology, 2021)
Stigma is integral to understanding mental health disparities among racial and ethnic minority groups in the United States. We conducted a systematic review to identify empirical studies on cultural aspects of mental illness stigma (public, structural, affiliative, self) among three racial and ethnic minority groups (Asian Americans, Black Americans, Latinx Americans) from 1990 to 2019, yielding 97 articles. In comparison studies (N = 25), racial and ethnic minority groups often expressed greater public and/or self‐stigma than White American groups. In within‐group studies (N = 65; Asian American, n = 21; Black American, n = 18; Latinx American; n = 26), which were primarily qualitative (73%), four major cultural themes emerged: 1) service barriers including access and quality (structural stigma); 2) family experiences including concealment for family’s sake, fear of being a burden, and stigma extending to family (affiliative stigma); 3) lack of knowledge about mental illness and specific cultural beliefs (public stigma); and 4) negative emotional responses and coping (self‐stigma). These findings confirmed stigma has both similar and unique cultural aspects across groups. Despite this, few studies tested stigma reduction interventions (N = 7). These cultural insights can inform contextual change at the health systems and community levels to reduce stigma, and empowerment at the interpersonal and individual levels to resist stigma. Highlights We identified cultural aspects of mental illness stigma among Asian, Black, and Latinx Americans Stigma tended to be higher among the racial and ethnic minority groups than White comparison groups Stigma has similar and unique cultural aspects across the three racial and ethnic minority groups Major themes were service barriers, family experiences, knowledge/beliefs, and emotional responses Interventions can integrate cultural aspects to reduce service barriers and target stigma directly